The utilization of Tepache Probiotic Drink for health benefits and creating household-scale economic opportunities - Titta Novianti; Seprianto Seprianto; Rini Hidayati (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
Probiotic drinks are needed to enrich the microbiome in the digestive organs. Increasing age causes a decrease in the ability of cells to metabolize food, resulting in various degenerative diseases. Tepache probiotic drinks, made from pineapple skin, contain magnesium minerals for bone health, vitamins A, B, and C. Through fermentation, it is enriched by lactic acid bacteria which play a role in helping food metabolism in the intestines and increasing the immune response. Counseling on making tepache probiotic drinks for Family Empowerment and Welfare (PKK) mothers RW 11 Pamulang Timur is expected to improve public health and stimulate the household economy. The method of implementing community service is carried out by means of socialization of the benefits of probiotic drinks, training in making tepache probiotic drinks, financial management and marketing training, and production assistance. Tepache drinks are made from pineapple skin fermented for 24 hours using brown sugar, water, cloves, and cinnamon. The success of fermentation is indicated by the presence of white grains on the surface of the liquid. The fermentation results are filtered and can be consumed directly. The results of the counseling produced a tepache drink product that has been routinely consumed by PKK mothers RW 11 Pamulang Timur, and has an impact on reducing knee pain, tension, blood sugar, uric acid, and cholesterol. The results of household-scale sales have not shown significant profits, but simple calculations if pursued will increase household income.